Internal Focalization through a Child’s Perspective in a Movie - Hereera, Rina Saraswati; Heriyati, Nungki (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The purpose of this study is to examine how internal focalization techniques in the film The Boy in the Striped Pajamas can create dramatic irony conveyed through the perspective of an eight-year-old child whose knowledge is innocent and limited, namely Bruno. This study analyzes specific dialogues and also includes visual elements in the film using a qualitative descriptive approach. From this study, the results show that dramatic irony can be present through Bruno’s misunderstandings, how he interprets the concentration camp, the uniforms used by prisoners, the numbers on the prisoners’ clothes, and the crematorium smoke which he assumes is caused by burning "hay." Additionally, historical trauma is also subtly conveyed in this film, highlighting the suffering of Jewish people due to the Holocaust which impacts subsequent generations. The difference between Bruno’s understanding and the audience’s knowledge presents a strong emotional effect, with tension and sadness as well as the historical trauma present in the film.